Use of HEPG2 cells to assay the safety of cosmetic active substances - Chiari, Bruna Galdorfini [UNESP]; Martini, Paula Cressoni [UNESP]; Moraes, Jemima Daniela Dias [UNESP]; Andréo, Rogério [UNESP]; Correa, Marcos Antonio [UNESP]; Cicarelli, Regina Maria Barretto [UNESP]; Isaac, Vera Lucia Borges [UNESP] (My University, 2012)
The importance of this study is based on the need to obtain simple and efficient in vitro models to predict the in vivo toxicity of cosmetics, aiming not to use animals as experimental model. Here, we proposed the use of HepG2 cells, which are widely applied to simulate the hepatic function of the human organism in vitro. This cell line was chose since recent studies have shown that the liver is potentially the most frequently targeted organ by cosmetic ingredients, and beyond that, considering the widely application of in vitro assays to test the cutaneous permeation of cosmetic products, including the assays applying modified Franz cells, this technique becomes indispensable. Three different cosmetic active substances were used, and the toxicity to HepG2 cells was assessed by the MTT method. The treatment with hyaluronic acid showed no toxicity to HepG2 cells. Treating the cells with P. guajava L. extract were verified that increasing the amount of the extract in the media, the cellular viability decreased, and finally, the treatment of alpha-lipoic acid showed a cytoprotective effect in relation to the treatment with propylene glycol. The study demonstrated the suitability in using HepG2 cells to assess the safety of cosmetic active substances, helping in the prediction of if the substance could be hepatotoxic if could reach the bloodstream
Keywords: HepG2; citotoxicity